PERMINTAAN KUBIS PADA SEGMEN KONSUMEN MAHASISWA UNIVERSITAS TRIBHUWANA TUNGGADEWI DI PASAR LANDUNGSARI KABUPATEN MALANG - Soni, Apolonius; Asnah, Asnah; Rofiatin, Umi (BUANA SAINS, 2023)
Demand is the number of goods requested at various price levels in a certain period so the price variable is a variable that influences demand. This study aims to analyze the demand for cabbage by Tribhuwana Tunggadewi University students, Malang City, at Landungsari Market, Malang Regency. Location determination was carried out purposively, with a total sample of 100 people determined by simple random sampling. The data analysis method uses demand function analysis with SPSS version 22 software. The results show that the data is normally distributed, and there are no deviations from the classical assumptions, both multicollinearity, and heteroscedasticity, so the selected model can be used properly and is not biased with Adjusted R Square 0.849. Selected independent variables have a significant effect simultaneously on the dependent variable. While partially the demand for cabbage in this study was significantly influenced by the price of the cabbage itself, the price of chicory, the price of mustard greens, and consumer tastes